Memamfaatkan Media Sosial Untuk Mengedukasi Generasi Z Mengenai Etika Kristen Di Era Digital - Lius Ade Boy Nazara (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This study aims to investigate the potential of social media in facilitating education about Christian ethics for Generation Z in the digital era. Generation Z is a group that has grown up amid advances in information technology and the widespread spread of social media. This raises new challenges in educating them about Christian ethical values.s This research will use a qualitative approach with the case study method. Data will be collected through in-depth interviews with young generation Z who actively use social media and have a Christian religious background. In addition, an analysis of relevant social media content will also be carried out to understand the use of social media in the context of Christian ethics education. The results of this study are expected to provide better insight into how social media can be used effectively to educate Generation Z about Christian ethics. These findings can be the basis for developing educational strategies that are more adaptive and relevant to the characteristics of the digital-savvy Generation Z. In addition, this research is expected to contribute to overcoming the challenges faced by churches and Christian educational institutions in facing the ever-evolving digital era. By using social media as an educational tool, churches and Christian educational institutions can reach Generation Z more effectively and provide a deeper understanding of Christian ethics.